Development by Genetic Immunization of Monovalent Antibodies Against Human Vasoactive Intestinal Peptide Receptor 1 (VPAC1), New Innovative, and Versatile Tools to Study VPAC1 Receptor Function - Peyrassol, Xavier; Laeremans, Toon; Lahura, Vannessa; Debulpaep, Maja; El Hassan, Hassan; Steyaert, Jan; Parmentier, Marc; Langer, Ingrid (Frontiers in Endocrinology, 2018)
Multi-membrane spanning proteins, such as G protein–coupled receptors (GPCRs) and ion channels, are extremely difficult to purify as native proteins. Consequently, the generation of antibodies that recognize the native conformation can be challenging. By combining genetic immunization, phage display and biopanning, we identified a panel of monovalent antibodies (nanobodies) targeting the VPAC1 receptor. The nine unique nanobodies, that were classified into four different families based on their CDR3 amino acid sequence and length, were highly specific for the human receptor and bind VPAC1 with moderate affinity. They all recognize a similar epitope localized in the extracellular N-terminal domain of the receptor and distinct from the orthosteric binding site. In agreement with binding studies, which showed that the nanobodies did not interfere with VIP binding, all nanobodies were devoid of any functional properties. However, we observed that the binding of two nanobodies was slightly increased in the presence of VPAC1 agonists (VIP and PACAP-27), but decreased in the presence of VPAC1 antagonist. As no evidence of allosteric activity was seen in VIP binding studies nor in functional assays, it is therefore possible that the two nanobodies may behave as very weak allosteric modulators of VPAC1, detectable only in some sensitive settings but not in others. We demonstrated that the fluorescently labeled nanobodies detect VPAC1 on the surface of human leukocytes as efficiently as a reference mouse monoclonal antibody. We also developed a protocol allowing efficient detection of VPAC1 by immunohistochemistry in paraffin-embedded human gastrointestinal tissue sections. Thus, these nanobodies constitute new original tools to further investigate the role of VPAC1 in physiological and pathological conditions.